Development and validation of a tahfiz school performance index - Othman, Azam; Nik Abdullah, Nik Md. Saiful Azizi; Ruslan, Norbaiduri; Nordin, Mohamad Sahari; Shabu, Shahrul Fhaizal (IIUM Press, International Islamic University Malaysia, 2024)
The Tahfiz (Qur’an memorisation ) School Performance Index was developed as a tool to measure the performance of Tahfiz Schools in several key areas of Tahfiz education and sustainable growth development. The constructs assessed in the index were developed from analyses of focus group discussions with a few groups of stakeholders. The self-developed constructs were presented to several subject matter experts in the area of Islamic education to ascertain their face and content validity. For construct validity, the index was tested on a sample of 1,384 respondents, comprising Tahfiz school administrators, teachers, and alumni, and analysed using the Rasch Rating Scale Model. The results generated some evidence of construct validity, although some items related to Tahfiz education showed some misfitting. The index could potentially be used to measure and improve the quality of the Tahfiz education sector . The index combines aspects of Tahfiz education with elements of Sustainable Growth Development to offer a holistic overview of the progress and well-being of the community within a Tahfiz School. This study however only focused on one type of Tahfiz School, which is Academic Tahfiz Schools, a type of Tahfiz school that teaches academic school subjects, Islamic education subjects, and Qur’an memorisation, and excluded other types of Tahfiz schools such as fully traditional Tahfiz schools.